SOME PROPERTIES OF ANALYTIC FUNCTIONS DEFINED BY A NEW INTEGRAL OPERATOR - S R, AMITH (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
The object of the present paper is to derive some properties of analytic functions in the open unit disc which are defined by using new integral operator based on differential subordination technique. Key words and phrases: Analytic functions, Differential subordination, Integral operator. 2000 Mathematics Subject Classification: 30C45.